Elites Universitarias y Cambio Climático - Parker-Gumucio, C (2012)
Measures to address climate change on the planet involve a number of factors including the existence of structures and organizations to catalyze and encourage transformative actions. Local capacity building involves the consciousness of citizens and elites in line with the institutional actions to respond at various levels. Based on empirical research the orientations of the elite university students in Chile are analyzed. We focus on the perceptions of climate change, adaptation and / or mitigation measures and the vision of non-conventional renewable energy one of the main factors that may influence the reduction of emissions of greenhouse gases.